MECHANICAL CHARACTERISTIC STUDY OF COBALT ALLOY PREPARED BY POWDER METALLURGY METHOD - Aminatun, Aminatun; Ady, Jan; KD, Mega Farynda (Indonesian Applied Physics Letters, 2020)
This study was conducted to determine the effect of compaction pressure and sintering temperature variations on the properties of physical, mechanical, and micro cobalt alloy. Manufacture of the cobalt alloy with compositions 63,75%, chromium 30%, molybdenum 5%, manganese 0,5%, silicon 0,5%, and 0,25% nitrogen using powder metallurgy method. Variations of compaction pressure were 339,70 MPa, 396,31 MPa, dan 452,93 MPa, and sintered at temperature 12000C and 130 0C for 2 hours of holding time. Density was increased along with the increasing compaction pressure and sintering temperature (3,9-6,6 g/cm). The hardness was also increased along with the increasing compaction pressure and sintering temperature  205,1-316,2 VHN. XRD results showed that Î³ phase with fcc structure was formed at the temperature of 12000C and 13000C for all variations of pressure. SEM-EDX results showed that the oxygen content decreased along with increasing compaction pressure and sintering temperature. Based on ASTM F75 hardness standard, the sample with compaction pressure 452,93 MPa and sintered at 13000C was the best cobalt alloy with a hardness value of 316.2 VHN.